The Analysis of Athletic Sports Coaching Management in East Java, Indonesia: A Systematic Review - Erdilanita, Ulma; Mulyana, Mulyana; Widiawati, Prisca (Indonesian Journal of Sport Management, 2025)
Background: Athletics is vital for national identity and development, yet Indonesia faces challenges in achieving consistent success. In East Java, issues such as inadequate infrastructure, low athlete motivation, and insufficient coach competency hinder athletic performance. Purpose: The aim of this research is to analyze the coaching management to improve the management and performance of athletics. Methods: A systematic review was conducted using the PICO approach and PRISMA Flow diagram. Articles from 2019 to 2023 were sourced from Google Scholar using keywords like "manajemen pembinaan" AND "atletik" and "coaching management" AND "Athletic". From 340 articles, 11 met the criteria after screening. Results: The review of 11 articles resulted in 4 articles stated that the infrastructure was not met the standard yet, 6 articles indicated the low interest and motivation of athletes in training to improve their achievements in athletics, and 7 articles stated that there was a lack of competence, knowledge, skills, supervision or assistance from the coaches. Implication and Recommendations: Significant improvements are needed in East Java's athletic coaching management, particularly in upgrading sports facilities, providing coach training, enhancing athlete motivation, and strengthening management structures. Addressing these areas can improve athletic performance, foster talent development, and contribute to Indonesia's success in national and international sports. Keywords : Athletic; Coaching; Sport management; Training center